Prevalence and risk of cognitive impairment among patients with asthma: A systematic review and meta‐analysis - Ganesh Bushi; Mahalaqua Nazli Khatib; Shilpa Gaidhane; Renuka Jyothi. S; Manish Srivastava; Apurva Koul; M. Ravi Kumar; Quazi Syed Zahiruddin; Sarvesh Rustagi; Sanjit Sah; Hashem Abu Serhan; Muhammed Shabil (Brain and Behavior)
Abstract Background Asthma, a prevalent chronic respiratory condition, is hypothesized to influence cognitive health; however, the precise nature of this association remains unclear. This systematic review and meta‐analysis aimed to elucidate the prevalence and risk of cognitive impairment in individuals with asthma. Methods A comprehensive literature search was performed in databases such as PubMed, EMBASE, and Web of Science, spanning publications up to December 25, 2023. This search aimed to identify studies that assessed cognitive impairment in patients with asthma. We used the random effects model in the R v4.3 software for the meta‐analysis to evaluate the prevalence and risk of cognitive decline, including dementia and Alzheimer's disease, among asthma patients. To ensure robustness and validity, the quality of the studies was assessed using Newcastle–Ottawa scale. Results Twelve studies met the inclusion criteria, of these 10 were eligible for meta‐analysis. The pooled prevalence of cognitive impairment in patients with asthma was 16.3%. The analysis also revealed an increased hazard ratio of 1.47 (95% confidence interval [1.09; 1.84]) for cognitive impairment in patients with asthma compared to the control group (individuals without asthma). Significant heterogeneity and publication bias were observed across the studies. The results underscored the substantial correlation between asthma and heightened risks of cognitive decline, dementia, and Alzheimer's disease. Conclusion This review found a notable association between asthma and an increased risk of cognitive decline, including dementia and Alzheimer's disease. These findings highlight the importance of integrating cognitive health assessments into asthma care. Further research is required to understand this relationship and develop effective treatments. Emphasizing a holistic approach to asthma management, these findings highlight the need to consider both respiratory and cognitive health for comprehensive patient care.